Impact of burnout among dialysis nurses providing high-quality care in Butuan City, The Philippines - B. Cecelle . Butao; D. G. Arquiola; M. J. Talidro; B. C. K. Donoso; S. R. L. Mongado; N. P. Funcion; A. D. Gumanoy; Stephen Ayoade Fadare (Orapuh, Inc., 2021)
Introduction Hemodialysis (HD) nurses are prone to multiple and more overt forms of stress that could eventually lead to burnout. Burnout has detrimental effects on affected nurses and may jeopardize patient welfare and quality of treatment. Purpose The purpose of this study was to assess burnout among nurses working at the dialysis centers of Butuan City, The Philippines and its impact on providing high-quality nursing care to their patients. Materials and methods The researchers surveyed the six hemodialysis centers in Butuan City, Agusan Del Norte, The Philippines. The study participants were forty-four (44) hemodialysis nurses. The researchers used a four-part questionnaire to examine burnout and nursing care quality. The questionnaire was used to assess the impact of burnout on hemodialysis nurses and the quality of nursing care. The parameters used included the extent of interpersonal and intrapersonal factors that modify burnout and the relationship between burnout and nursing care quality. Results The results showed that most of the respondents were between the ages of 26 and 30 years (29.55%), female (70.45%), single (65.90%), and have 1-3 years of hemodialysis work experience (45.5%). These demographic characteristics of the respondents implied that female HD nurses outnumbered their male counterparts in Butuan City. The results also indicated that there was no statistically significant difference between the intrapersonal and interpersonal factors of burnout and the respondents' demographic profiles (p>0.05). There was, also, no significant association between the quality of nursing care and reduced personal achievement (r = 0.00042). However, there was a significant association between the quality of nursing care and emotional exhaustion and depersonalization (r = 0.517 and r = 0.419, respectively). Conclusions Burnout has a significant impact on the quality of nursing care among hemodialysis nurses of Butuan City, The Philippines. HD nurses must focus on developing workplace practices that will help to reduce burnout and empower them to foster healthy connections with their co-workers. This provides a peaceful and productive work environment that may help ease tensions and burnout.